Comparison of flow cytometric and immunohistochemical immunophenotyping data for diagnosis of B-cell neoplasms and classic hodgkin's lymphoma - Fatma Saeed Alqahtani; Karim Hamda Farhat; Mashael Marzouq Alshebly (Wolters Kluwer Medknow Publications, 2019)
Objective: This study was aimed to compare the results of immunophenotyping by flow cytometry (FC) and immunohistochemistry (IHC) in the diagnosis of B-cell lymphomas and classic Hodgkin's lymphoma (cHL). Methods: This was a retrospective cohort study of 280 patients with chronic B-cell neoplasms and cHL performed between 2008 and 2013. Percentages of B- and T-cell markers detected by FC and IHC were compared regardless of the final diagnosis. Results: FC and IHC results were obtained from 280 patient medical records. There were 155 (55.4%) patients with non-Hodgkin's lymphoma (NHL), 110 (39.3%) with cHL, and 15 (5.4%) with chronic lymphocytic leukemia (CLL). Disparity between FC and IHC was observed for CD19 expression in cHL group where 73.6% (n = 81) CD19 expression was detected by FC and 59.1% (n = 65) detected by IHC (P < 0.02). In NHL group, a higher percentage (81.3%; n = 126) of CD19 was detected by FC as opposed to 61.3% (n = 95) detected by IHC (P < 0.0001). CD19 expression was no different between the two groups. CD20 expression assessed by FC (61.3%; n = 95) was lower than 85.2% (n = 132) detected by IHC in NHL group (P < 0.0001). Whereas no differences were observed in cHL, IHC performed better (100%; n = 15) than FC (66.7%; n = 10) for CD20 detection in CLL group (P < 0.01). In cHL and NHL groups, flow cytometric detections of CD21 of 61.8% and 56.1% were higher than 46.4% (P < 0.02) and 41.9% (P < 0.01) detection rates by IHC. No disparities were observed between FC and IHC detection rates for CD5, CD10, CD23, and CD30 expressions. Conclusion: There was a considerable amount of disparity between FC and IHC results, warranting further evaluation.